Development of mathematical literacy instruments using batik Banten context for junior high school - Adillaningtyas, Pravista; Syamsuri, Syamsuri (Universitas Sultan Ageng Tirtayasa, 2024)
This research aims to develop and see the potential impact of a valid and reliable mathematical literacy instrument using the Banten Batik context for junior high school students. The subjects of this research were junior high school students at SMPN 7 Serang City. This research uses the Research and Development (R&D) Plomp model which consists of 5 stages, namely self evaluation, expert reviews, one to one, small group, and field test. This research produced eight mathematical literacy instruments using the Banten Batik context which correspond to the level of mathematical literacy according to PISA and are valid and reliable. The instrument developed has a potential impact seen from students' ability to: (1) use basic algorithms, formulas and procedures, (2) follow instructions that have been given, (3) explain an operation and respond in a simple systematic form, (4) demonstrate understanding basics about functional relationships, (5) interpreting and using representations, (6) solving problems with undefined models obtained from reasoning abilities, (7) designing procedures through combining mathematical knowledge that is not stated explicitly in the problem, (8) mastering symbolic mathematical operations and formal and can explain the reasons for decision making in relation to the initial solution and problem.